Cardiovascular death in kidney recipients treated with renin-angiotensin system blockers - Opelz, Gerhard; Döhler, Bernd (Transplantation, 2014)
BACKGROUND: Angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) are widely prescribed after kidney transplantation, but evidence for an improvement in outcomes is mixed. A recent trial demonstrated a significantly lower incidence of major cardiovascular events in ACEI-treated recipients. - METHODS: Collaborative Transplant Study data on cardiovascular death during years 2 to 10 after kidney transplantation in patients with a functioning graft were analyzed according to whether ACEI/ARB or other antihypertensive therapy (excluding diuretics) was administered at year 1. - RESULTS: Of 39,251 transplants analyzed, 15,250 (38.9%) received ACEI/ARB and 24,001 (61.1%) received other antihypertensive therapy at year 1 after transplantation. The mean duration of follow-up was 5.8 years. During years 2 to 10 after transplantation, cardiovascular death occurred in 918 patients (cumulative incidence=4.7%) with a functioning graft. The rate of cardiovascular death was similar in patients who received ACEI/ARB therapy or other antihypertensive treatment overall and in subpopulations of patients who were considered by the transplant center to be at an increased cardiovascular risk, had no pretransplant risk factors, were aged 60 years and older, were treated for diabetes at year 1, or had serum creatinine of 130 μmol/L or higher at year 1. Multivariable Cox regression analysis confirmed that treatment with ACEI/ARB did not confer a beneficial effect beyond that conferred by other antihypertensive treatments on the cumulative incidence of cardiovascular death during years 2 to 10 (hazard ratio=1.1, P=0.24). - CONCLUSIONS: This large-scale retrospective analysis of prospectively collected data shows that the rate of cardiovascular death in kidney transplant recipients receiving ACEI/ARB or other antihypertensive medications is virtually identical.
Gesehen am 24.09.2020